PROBLEMS AND OBSTACLES IN FILING AND FILING TAX RETURNS THROUGH THE SYSTEM INTERNET OF PERSONNEL WITHIN KHON KAEN IRRIGATION PROJECT - Niamprem, Sanya; Chuenpiboon, Wananporn; Tapimai, Maychaya; SiriKaew, Kanokwan (Journal of Liberal Arts and Management Science Kasetsart University, 2020)
This research is a survey research. With the objective to study the problems and obstacles in filing returns and paying personal income tax through the internet of personnel within Khon Kaen Irrigation Project. The population used in this research are personnel in Khon Kaen Irrigation Project, a total of 106 people. Research instruments are questionnaires. Using descriptive statistics to analyze data. The research findings were showed problem and obstacles in filing returns and paying personal income tax through the internet of personnel within Khon Kaen Irrigation Project. The highest average aspect is the complex approval and filing process, causing delays. The second is the lack of knowledge and understanding of the internet filing system. The lowest average side is the error side during system filing. In addition, the result also found that the factors that affect the problem and obstacles in filing returns and paying personal income tax through the internet of personnel including, age, receiving advice affects the knowledge and understanding, and confidence in filing and paying taxes online. Therefore to reduce such obstacles, project personnel should be trained to increase confidence in online filling and tax payment systems. should be train personnel to understand and be confident in both the network and information services, including providing staff with information about filing and paying taxes online.